Students' Self-Regulated Learning During Online Learning In Vocational High School Bandung - Rizal Aminulloh; Al Jupri; Dadang Juandi (IKIP Siliwangi, 2021)
This study aims to obtain student responses and opinions regarding self-regulated learning of students during the Covid 19 pandemic in online learning at SMK Negeri 1 Bandung seen by grade level and also by major. This study used descriptive quantitative research methods. The population in this study were all students of SMKN 1 Bandung from tenth to twelve grade. Sample selection using snowball sampling technique. The results shows that the average score of respondents on the learning independence of SMKN 1 Bandung students during the Covid 19 pandemic was 3.78. Based on the results, we can concludes that the level of independence of SMKN 1 Bandung students in online learning during the pandemic is in the criteria of being quite independent.